2016
DOI: 10.1177/1350650115592919
|View full text |Cite
|
Sign up to set email alerts
|

Design of an axially concave pad profile for a large turbine tilting-pad bearing

Abstract: To improve operational safety and/or achieve a higher load capacity of turbine tilting-pad bearings, an axially concave pad profile is presented. The thermal and mechanical stress of the loaded pads of a test bearing in load between pivot configuration has been analysed. Both film thickness and pressure distribution have been measured at a very high resolution. A fluid film calculation program in combination with a finite-volume-based structural mechanics program is used to simulate the deformation of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The calculation procedure and the results are also discussed in the publications of Hagemann et al [16] and Kukla et al [17] and show good agreement between calculation results and experimental data. Kukla et al [18] apply an optimization procedure to the same ∅-500 mm five-pad TPJB already used by Hagemann [5]. They determine the HTC at the free pad surfaces by minimizing the deviations between measured and calculated measuring point temperatures.…”
Section: Heat Transfer In Journal Bearingsmentioning
confidence: 99%
“…The calculation procedure and the results are also discussed in the publications of Hagemann et al [16] and Kukla et al [17] and show good agreement between calculation results and experimental data. Kukla et al [18] apply an optimization procedure to the same ∅-500 mm five-pad TPJB already used by Hagemann [5]. They determine the HTC at the free pad surfaces by minimizing the deviations between measured and calculated measuring point temperatures.…”
Section: Heat Transfer In Journal Bearingsmentioning
confidence: 99%
“…The study results have shown that reduction of bearing surface temperature achieved by optimized vortex grooves resulted in a significant increase in bearing capacity. Thermal deformations of slider bearing pads of a powerful turbine are considered in [13]. Comparison of measurement data and calculations is given which showed good conformance for thermal deformations in pads.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Elastic deformations of the segments were calculated using expressions (5), (13), and (15). Deformations were calculated for the most loaded lower segment in which pressure in the chambers at large eccentricities was close to the feeding pressure of the working fluid.…”
Section: Determining the Segment Deformation In Circumferential And Axial Directions Under The Action Of A Distributed Load On Itmentioning
confidence: 99%
“…The models of Furtmann [1,2] and Gemeinder [3] are based on the consideration of the loaded rolling elements only; Schirra extends the approach by including the load-free rolling element contacts for sensory purposes [6,7]. For journal bearings, due to the absence of rolling elements and the rather plain bearing surfaces, more sophisticated models, such as the cylinder capacitor, can be used to achieve a good agreement between model predictions and test rig measurements, e.g., for the lubricating film thickness or other operation conditions [8][9][10][11]. However, such methods cannot be used for insulating coatings, such as those found in tilting pad bearings with, e.g., PEEK thrust pads forming an extra capacitor arranged in series with the lubrication film.…”
mentioning
confidence: 99%